2023
DOI: 10.4081/jphia.2023.2242
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 wave was already here: High seroprevalence of SARS-CoV-2 antibodies among staff and students in a Cameroon University

Abstract: Background: Seroprevalence studies, to estimate the proportion of people that has been infected by SARS-CoV-2 are importance in African countries, where incidence is among the lowest in the world. Objective: This study aimed at evaluating the exposure to SARS-CoV-2 within a university setting of Cameroon.Methods: A cross-sectional study performed in December 2020 - December 2021, among students and staffs of the Evangelical University of Cameroon. COVID-19 antigen rapid detection test (RDT) was performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
0
6
1
Order By: Relevance
“…This might be justified by the fact that young males are more socially actives than females, visiting crowded areas like bars and practicing contact games like football which will increase the risk of SARS‐CoV‐2 transmission. The anti‐SARS‐CoV‐2 antibodies prevalence in university student population found in this study was higher compared with what reported by Voundi et al 7 (4.6%) among a student community in Yaoundé but less than the one obtained by Wondeu et al 2 among staff and student in a Cameroon university in Bandjoun (75.5%). This difference could be justified in one hand by sample size of our study (547) as compared with that of Voundi et al (11549) and Wondeu et al (106).…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…This might be justified by the fact that young males are more socially actives than females, visiting crowded areas like bars and practicing contact games like football which will increase the risk of SARS‐CoV‐2 transmission. The anti‐SARS‐CoV‐2 antibodies prevalence in university student population found in this study was higher compared with what reported by Voundi et al 7 (4.6%) among a student community in Yaoundé but less than the one obtained by Wondeu et al 2 among staff and student in a Cameroon university in Bandjoun (75.5%). This difference could be justified in one hand by sample size of our study (547) as compared with that of Voundi et al (11549) and Wondeu et al (106).…”
Section: Discussioncontrasting
confidence: 82%
“…In Cameroon, few seroprevalence studies have been conducted in university settings 2,7 . However, no published data estimate the seroprevalence in a university community during the second wave of infection in Cameroon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…in a community-based study from Yaoundé (24%) [ 34 ], Deutou Wondeu et al . among university staff and students (71.3%) in Bandjoun, a kingdom in the West Region of Cameroon [ 37 ], Sandie et al . among blood donors from Douala and Yaoundé (66.3% to 98.4%) [ 38 ], and Diallo et al .…”
Section: Discussionmentioning
confidence: 99%